AN APPLICATION OF MOTION CORRECTION METHODS TO THE ALIGNMENT PROBLEM IN NAVIGATION - Boris I. Ananyev (Ural Mathematical Journal)
In this paper, we apply some motion correction methods to the alignment problem in navigation. This problem consists in matching two coordinate systems having the common origins. As a rule, one of the systems named as basic coordinate system is located at a ship or airplane. The dependent coordinate system belongs to another object (e.g. missile) that starts from the ship. The problem is considered with incomplete information on state coordinates which can be measured with disturbances without statistical description.